Pelatihan Identifikasi Potensi Desa Temas Kabupaten Rote Ndao Nusa Tenggara Timur Dalam Upaya Pemberdayaan Masyarakat - Makleat, Nirwaning; Mardani, Ambara Saraswati; Neonufa, Samrid; Simbolon, Gallex; Selly, Frans K. (Jurnal Pengabdian UNDIKMA, 2023)
This service aims to provide knowledge and competence for the people of Temas Village to identify the village’s potential to realize community welfare. The method used in this service was participatory training with experience sharing, practice, and discussion techniques. These service partners were the village head, village apparatus, and the Temas Village Community, Rote Ndao Regency, Nusa Tenggara Timur. The evaluation instruments for this activity were the pretest and posttest, and were analyzed descriptively. The results of this dedication showed that the training was carried out well so that the Village Government and the community could identify and map the village’s potential to create community welfare.